Transparency Still Valuable When Budget Details Are Wrong? - Tri Diana Sari; Nuri Susilawati; Teguh Wahyudi; Masita Nur Hayati (International Journal of Economics, Business and Innovation Research, 2024)
This research aims to explore how universities use budgets to achieve their goals. Using a qualitative approach, we interviewed the deputy dean responsible for managing the university budget and the head of planning and budgeting to explain how they interpreted the 2023 budget to achieve the university's goals. Based on their statements, this research found that there were inconsistencies, meaningless words, and ambiguous descriptions but the aim remained the same. So our findings suggest that objectives become unimportant when the budget is irrelevant, transparency becomes useless due to incorrect budget details.